A Learning-by-Doing Approach to Entrepreneurship Education: Evidence from a Short Intensive Online International Program - Alessandra Colombelli; Andrea Panelli; Francesco Serraino (Administrative Sciences, 2022)
Entrepreneurship is considered a key driver for economic growth. Therefore, more and more studies are investigating the role and effectiveness of entrepreneurship education. In this context, the present study is aimed at investigating the effectiveness of entrepreneurship programs, with a learning-by-doing approach, on the entrepreneurial intention, entrepreneurial characteristics (entrepreneurial attitude, entrepreneurial self-efficacy, entrepreneurial mindset, core self-evaluation) and entrepreneurial skills (creativity, financial literacy, marshaling of resources, planning, teamwork). The study has analyzed a short intensive online entrepreneurship program, which adopts a learning-by-doing approach and targets students from different European technical universities, with different levels of education and different entrepreneurial backgrounds, giving them the opportunity to work on different types of projects. Pre- and post-course surveys were conducted in order to perform qualitative analyses on the effectiveness of the program. The results show that the entrepreneurial intention and perception of the entrepreneurial characteristics and skills of the students increased after participation in the program. In addition, our findings reveal that the program appears to be more effective for MSc students than for PhD ones and for students who had never attended any entrepreneurship program before, while there is no difference in the effectiveness of the program in terms of gender.